Desain Strategi Pengelolaan Green Campus Pada Universitas Pattimura - Martha Amba (Industrial Engineering Study Program, Pattimura University, 2015)
Environment, especially in urban areas or places where people do their activities need to kept safe and comfortable for the survival of people who move in it. The Pattimura University campus which currently holds about 20.444 students requires environment that remain comfortable and beautiful to be occupied by academicians, educators and students. Green Campus strategies should be developed by analyzing the factors that influence both internal and external. By using SWOT analysis, results of the research show that the index factor was 0.51 strengths and weaknesses, and opportunities and threats factor index is 0.68, which means that this university in aggressive position: strengths can eliminate weaknesses and opportunities will minimize the threat. Determining the optimal strategy is calculated by using QSPM. S- O strategy is to create an academic community participation and education personnel organized through the green campus-based activities with TAS value = 6,32. W-O strategy is green campus of the application of the policy through media relations and NGOs with TAS value = 6,58. S-T strategy is to make rules and guidelines for the campus management with the concept of a green campus, TAS value = 6,31. W-T strategy is carry out research on the campus environmentally sustainable with TAS value = 6,11.